Anomalías dentarias en pacientes con labio leporino y paladar hendido - Jonathan Patricio, Torres España (2021)
ABSTRACT: The purpose of this bibliographic research was to identify frequent dental anomalies in patients with non-syndromic cleft lip and palate. For this research, a systematic review of scientific articles has been made, published in different databases such as PubMed, Scielo, Elsevier, and Google Scholar, between 2010 and 2020. It was taken into account that the articles collected comply with the ACC index. They are also registered in the SJR impact factor. They get the inclusion and exclusion criteria. A total of 41 articles were found, which after analyzing them were obtained, 30 articles with which the discusión and meta-analysis were carried out. With the different studies analysis, the conclusión was the dental anomalies that frequently affect this type of patients are hypodontia, microdontia, supernumerary teeth, gyroversions, impacted teeth, enamel hypoplasia, dilaceration, transposition, ectopic teeth, and taurodontism. Hypodontia stands out as the most prevalent anomaly among people with cleft lip and palate, the most affected teeth being the maxillary lateral incisor, the maxillary second premolar, and the mandibular second premolar. KEY WORDS: dental abnormalities, cleft lip, and palate.